2012
DOI: 10.3852/11-070
|View full text |Cite
|
Sign up to set email alerts
|

New teleomorph combinations in the entomopathogenic genusMetacordyceps

Abstract: The genus Metacordyceps contains arthropod pathogens in Clavicipitaceae (Hypocreales) that formerly were classified in Cordyceps sensu Kobayasi et Mains. Of the current arthropod pathogenic genera of Hypocreales, the genus Metacordyceps remains one of the most poorly understood and contains a number of teleomorphic morphologies convergent with species of Cordyceps s.s. (Cordycipitaceae) and Ophiocordyceps (Ophiocordycipitaceae). Of note, the anamorph genera Metarhizium and Pochonia were found to be associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 34 publications
0
71
0
1
Order By: Relevance
“…All positions containing gaps and missing data were eliminated. Presently described species is different from M. indigotica in morphology, taxonomical details, and host insect, as described by Kepler et al (2012). Morphological features such as stromata (Liu et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…All positions containing gaps and missing data were eliminated. Presently described species is different from M. indigotica in morphology, taxonomical details, and host insect, as described by Kepler et al (2012). Morphological features such as stromata (Liu et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…There are only 100 species with 5.8 S ITS sequence data and only 80 species have been studied using multi-gene phylogeny. Recent phylogenetic studies (Spatafora et al 2007, Sung et al 2007a, b, Kepler et al 2012a, b, 2013, based on multiple independent loci, have provided a greater level of resolution for this complex group of fungi. Therefore, a detailed systematic classification of Cordyceps and the family Clavicipitaceae based on multigene phylogenies is necessary to reflect the natural placement in Hypocreales (Maharachchikumbura et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More than 240 Cordyceps species have been placed into these six genera, but about half of Cordyceps sensu lato species need to be restudied and re-arranged (Sung et al 2007a). Sung et al (2007a) and (Kepler et al 2012a) suggested that there are 15 Metacordyceps species, while 14 epithets are assigned to Metacordyceps in Index Fungorum (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining sp. was first transferred from Cordyceps to Ophiocordyceps and then to Metacordyceps prior to transfer to Metarhizium (Sung et al 2007; Kepler et al 2012a, 2014). Two more Metacordyceps spp.…”
Section: Current Placement Of Cordyceps Spp Following Amendment Of Amentioning
confidence: 99%